Analisis Tingkat Kohesivitas Karyawan pada PT. Pelindo IV (Persero) Cabang Makassar - Hasan, Handayani; Yuliana, Leny; Anastasya, Lidya; Ridha, Achmad; Windarsari, Wiwin Riski (Indonesian Journal Publisher, 2025)
This study aims to analyze the level of employee cohesiveness at PT. Pelindo IV (Persero) Makassar Branch and identify the key factors influencing it. Employee cohesiveness is essential in fostering a collaborative work environment, increasing productivity, enhancing job satisfaction, and reducing turnover rates. This research employs a quantitative approach with a descriptive design. Data were collected through questionnaires distributed to 63 respondents, selected using the Slovin formula from a total population of 172 employees. The analysis includes validity and reliability tests, followed by index number analysis to measure the level of cohesiveness based on four key indicators: social strength, group unity, attractiveness, and teamwork. The findings reveal that employee cohesiveness at PT. Pelindo IV (Persero) Makassar Branch is at a high level. Transformational leadership and effective communication significantly contribute to fostering a cohesive workplace by strengthening teamwork, encouraging mutual support, and enhancing collaboration. The study concludes that strong employee cohesiveness creates a harmonious work environment, improves efficiency, and supports organizational goal achievement. It is recommended that the company continue to strengthen leadership strategies and promote open communication to maintain and further enhance cohesiveness within the organization. Future research should explore other industries and incorporate qualitative approaches to gain deeper insights into employee interactions and workplace dynamics.